A festa do bode rei na Paraíba: aspectos culinários e sanitários - Correia, Cristiane Bezerra Libório (2019)
The popular festivals can act like promoter of sustainable local development, because it moves the economy and recover and spread the cultural values. The manner the foods are consumed and marketed on it manifests the local culture, however, its usually presents dubious hygienic-sanitary quality. Then, this research aims to explore the role of marketed foods in the Festa do Bode Rei (Goat King Festival), the principal touristic event of Cabaceiras (semi-arid city in Paraiba state), in regional social development by the valorisation of local culture and the use of Caatinga endemic species, also to observe the hygienic-sanitary control in the food marketing points. Therefore, two different surveys were applied to merchants and public respectively, and technical visits to establishment and microbiologic analysis on the stuff were carried out. From this, it was found that the tourists are the majority in the Festa do Bode Rei, the public prefers to go to the booths and the food is one of relevant reason to them to take part of the festival, it was evident the typical regional culinary as well. The festival moves significantly the supply chain, although the native species haven’t been used and often they’re confused with exotic species. Related to hygienic-sanitary conditions, the physical aspects of restaurants and snack bars didn’t comply with the legal requirements and in the most of places, neither permanents nor booth the manipulators were in conformity. About the analysis results, the water in the booth had better quality than restaurants, in both them the meat, as raw as cooked, had microbiological quality that complies with Brazilian legislation. In conclusion, the foods served in the festival were in agreement with legal requirements, however the water quality of restaurants and the manipulation practices must became better. In general, the Festa do Bode Rei plays its role to assist the development of Cabaceiras and provides a resisting and transmission of culture.